Perceptions of the Learning Environment on the Relationship Between Stress and Burnout for Residents in an ACGME-I Accredited National Psychiatry Residency Program - Sum, Min Yi (J Grad Med Educ, 2019)
BACKGROUND: High rates of burnout have been reported in physicians in training, with contributing factors including stress, lack of coping skills, and attributes of the learning environment. The interrelationships among these factors and how they affect versus mitigate burnout in an international cohort of residents have not been studied. OBJECTIVE: We examined the interrelationships between stress, perceptions of the learning environment, and coping strategies used in a cohort of psychiatry residents in Singapore, using burnout as the dependent variable. We hypothesized that perceptions of the learning environment and coping strategies influence the relationship between residency-related stress and burnout in psychiatry residents. METHODS: From June 2016 to September 2017, 67 of 75 (89%) psychiatry residents from a single program in Singapore were assessed on their levels of stress and burnout, perceptions of their learning environment (including role autonomy, teaching, and social support), and the coping mechanisms they used. RESULTS: Psychiatry residents in this Singaporean program perceived their overall learning environment to be positive. Perceptions of the learning environment, not coping strategies, significantly mediated the relationship between stress and burnout. CONCLUSIONS: Findings from this study suggest that perceptions of the learning environment mediate the relationship between stress and burnout. Approaches to evaluate and improve resident perceptions of aspects of their learning environment may be an effective strategy to manage burnout in psychiatry residency programs.